Interleukin-37 suppresses tumor growth through inhibition of angiogenesis in non-small cell lung cancer. Issue 1 (December 2016) - Ge, Guanqun; Wang, Aiqin; Yang, Jingyue; Chen, Yan; Yang, Jin; Li, Yize; Xue, Yan
Abstract Background Interleukin-37 (IL-37), a newly identified member of the IL-1 family, has been known to play an immunosuppressive role in a variety of inflammatory disorders, but whether it participates in the regulation of pathogenesis of non-small cell lung cancer (NSCLC) has not been investigated. Methods Real-time polymerase chain reaction (PCR), western blotting, and immunohistochemical staining were employed to detect IL-37 expression in NSCLC tissues and corresponding adjacent tissues. The correlations between IL-37 expression and clinicopathological characteristics, prognosis were analyzed. Stable clone with overexpression of IL-37 was generated in H1299 cell lines. Cell growth, cell cycle and cell apoptosis assays were carried out for detecting proliferation and apoptosis of H1299 cells. The effects of IL-37 on NSCLC progression in vivo was performed in a xenografted lung tumor model in nude mice. The concentrations of IL-37 and VEGF in the s growth medium supernatants were quantified by ELISA. The antiangiogenic effect of IL-37 on HUVEC was measured by tube formation assay. Results IL-37 mRNA and protein expressions were significantly decreased in NSCLC tissues, and decreased intratumoral IL-37 expression was significantly associated with tumor state, TNM stage and poor prognosis in NSCLC patients. In addition, intratumoral IL-37 expression was an independent prognostic factors for Overall survival (hazard ratio = 2.047;P = 0.011). Overexpression of IL-37 exerted no direct effect on cell proliferation and apoptosis of H1299 lung cancer cells in vitro, but significantly inhibited tumor growth in a H1299 xenograft model in vivo. Furthermore, there was no significant change in immune cell infiltration in IL-37 over-expressing tumors; instead, we found decreased microvessel density (MVD) and VEGF levels in IL-37-expressing tumors. Additional studies showed IL-37 could directly inhibit HUVEC cells growth and capillary structure formation. Finally, we found that decreased IL-37 expression was associated with high MVD in NSCLC patients. Conclusions Our findings demonstrate a protective role for IL-37 in lung cancer development, possibly through inhibiting tumor angiogenesis. IL-37 could serve as a promising therapeutic target for NSCLC.